Pelatihan Fotografi Untuk Pemasaran Produk Kuliner Pekerja Migran Indonesia Di Singapura - Yuniarti, Dini; Rejeki, Marsudi Endang Sri; Ayu, Suci Musvita; Cahyani, Fikhi (Carmin: Journal of Community Service, 2023)
In addition to having a positive impact in the form of foreign exchange flows, Indonesian Migrant Workers also have a negative socio-economic impact. PMI's repeated return to work abroad is partly due to a lack of entrepreneurial will. To encourage an increase in the entrepreneurial abilities of Indonesian Migrant Workers after returning to Indonesia, there are good problems, one of which is in the field of marketing which is still lacking. For this reason, the solution offered strengthens marketing in the form of culinary product photography training. The purpose of this service is to provide knowledge and skills to Indonesian Migrant Workers PMI in Singapore on how to make attractive photos of culinary products for marketing materials. The activity was carried out using the photography training method. Implementation of community service at the Embassy of the Republic of Indonesia, Singapore on June 25, 2023. Based on the results of the evaluation and performance measurement of partners, it was found that migrant workers experienced increased knowledge and skills in producing attractive culinary photos for marketing.